Analisis Peran Kompensasi Non Finansial, Pelatihan, dan Motivasi terhadap Kinerja Karyawan Kontrak (Studi Pada PT Xacti) - Santi Rimadias; Indah Ratry Pandini (STIE Indonesia Banking School, 2017)
Growth conditions in the manufacturing sector increased by 2.06% from the previous year. These growth conditions affect the competitiveness of manufacturing companies, then employee performance becomes a matter that must be considered to maintain the competitiveness of the company. This study aims to analyze the performance of contract employees in manufacturing companies (PT. Xacti). This study uses some variables, such as nonfinancial compensation, training, and motivation to analyze the effect of contract employee performance. Data collection techniques using questionnaires with a sample of some contract employees (PT. Xacti). Data collected as many as 119 respondents by using Structural Equation Modeling (SEM) method. The results of the conclusion of this study are as follows: 1) Nonfinancial compensation proved to have a positive and significant influence on the Contract Employee Motivation at PT. Xacti, 2) Motivation has no positive effect on Contract Employee Performance at PT. Xacti, 3) Nonfinancial Compensation has no positive effect on Performance Contract Employees at PT. Xacti, 4) Training proved to have a positive and significant influence on Contract Employee Performance at PT. Xacti.